Effect of guanine to inosine substitution on stability of canonical DNA and RNA duplexes: molecular dynamics thermodynamics integration study - Krepl, Miroslav; Otyepka, Michal; Banáš, Pavel; Šponer, Jiří (The journal of physical chemistry. B, 2013)
Guanine to inosine (G → I) substitution has often been used to study various properties of nucleic acids. Inosine differs from guanine only by loss of the N2 amino group, while both bases have similar electrostatic potentials. Therefore, G → I substitution appears to be optimally suited to probe structural and thermodynamics effects of single H-bonds and atomic groups. However, recent experiments have revealed substantial difference in free energy impact of G → I substitution in the context of B-DNA and A-RNA canonical helices, suggesting that the free energy changes reflect context-dependent balance of energy contributions rather than intrinsic strength of a single H-bond. In the present study, we complement the experiments by free energy computations using thermodynamics integration method based on extended explicit solvent molecular dynamics simulations. The computations successfully reproduce the basic qualitative difference in free energy impact of G → I substitution in B-DNA and A-RNA helices although the magnitude of the effect is somewhat underestimated. The computations, however, do not reproduce the salt dependence of the free energy changes. We tentatively suggest that the different effect of G → I substitution in A-RNA and B-DNA may be related to different topologies of these helices, which affect the electrostatic interactions between the base pairs and the negatively charged backbone. Limitations of the computations are briefly discussed.
Keywords: osmolární koncentrace; Hydrogen Bonding; Guanine; vodíková vazba; DNA; simulace molekulární dynamiky; termodynamika; Nucleic Acid Conformation; Thermodynamics; Inosine; guanin; RNA; Molecular Dynamics Simulation; Osmolar Concentration; inosin; konformace nukleové kyseliny